Evaluating the Feasibility of a Flipbook-Based Physics Learning Media Integrated with Local Culture: A Case Study on Matter State Changes - Dwi Ayu Nurfaizah; Tien Aminatun; Fitriani Fitriani; Insih Wilujeng; Laifa Rahmawati; Yusman Wiyatmo (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of technology-based learning media with local cultural contexts remains limited in physics education, particularly in teaching abstract concepts such as matter state changes. This study aimed to evaluate the feasibility of an electronic flipbook integrated with local cultural potential and to assess student responses toward its use in physics learning. This research employed a research and development (RD) approach using the 4-D model (define, design, develop, and disseminate), limited to the development stage without classroom implementation. The validation process involved eight expert validators, while student responses were collected from 15 junior high school students. Data were obtained through validation sheets and student response questionnaires, then analyzed descriptively using percentage scores. Validation results indicated that the developed flipbook was highly feasible, with an average score of 90.75% across content, presentation, linguistic, and graphic aspects. Student responses also showed very positive evaluations, with an average score of 93.75%, particularly noting the media’s attractiveness, readability, and contextual integration with local culture. These findings confirm that the electronic flipbook is a valid and feasible medium for physics learning, offering both technological innovation and cultural relevance. The integration of local cultural elements enriched the contextualization of abstract physics concepts, aligning with constructivist learning principles. However, further classroom implementation is needed to evaluate its effectiveness in improving student learning outcomes. The developed flipbook is feasible as a culturally integrated physics learning medium. Future research should focus on large-scale trials to measure its impact on students’ conceptual understanding and motivation.